Oxford studies in normative ethics. Volume 2 - Timmons, Mark, 1951- (Oxford : Oxford University Press, 2013)
In this volume, leading philosophers advance our understanding of a wide range of moral issues and positions. The topics discussed include: Kantian intuitionism, welfarism, the objective standard of good, intention, permissibility and double effect, moral dumbfounding and moral stupidity, coercion and integrity, practical reason and morality, atomism, subjective normativity and action guidance, and Rawlsian self-respect.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Normativity (Ethics)